(untitled) (ENTHYMEMA, 2016)
In the wake of fin-de-siècle discoveries in the field of endocrinology, bodily glands and the hormones they produced featured prominently in the literary works, visual arts, and popular culture of early twentieth-century Europe. Experimental surgery promised rejuvenation and intellectual vitality through gland transplantation and grafting, while phenomena of all sorts began to be associated to hormone production in causal links—from bodily rhythms to behavioral patterns, from the pace of history to the trajectory of nations. Italo Svevo was fascinated by Basedow and Graves’s discoveries on the thyroid, a gland that was supposed to determine the speed and promptness of one’s body according to the amount of hormones it produced—hypothyroidism, or scarcity of hormones, would entail lethargic behavior and slow movements, while hyperthyroidism, or the abundant production of hormones, would lead to excessive activity and consumption. Through the analysis of an early short story by Svevo, “Doctor Menghi’s Drug” (ca. 1904), this paper addresses how the activity of the thyroid affects not only bodily rhythms, but also narrative time—intended as both the time of the story (diegetic time) and the pace of storytelling—and it explores how metabolic processes act as constraints for literary creativity by complicating narrative time and raising questions of narrative agency.